PEMBENTUKAN KARAKTER ANAK USIA DINI MELALUI PENDIDIKAN PARENTING DI SEKOLAH - Muruatul Afifah; Achmad Maulidi; Najmi Faza (Irfani, 2021)
The role of parents is very important in shaping and developing the character of children. Therefore, the school should be able to create a good collaboration with parents. Through parenting education in schools is expected to maximize the role of parents in the building of strenghten student's character. This research was conducted at RA Nurul Huda Kalibaru, Banyuwangi. This study used the qualitative approach with the descriptive methods of analysis and case studies. The data was collected by using observation, interview and documentation techniques. The results of the research on Character Building through Parenting Education in Schools are: 1) The school makes sharing of parenting even with the parents and school committees to establish the mutual commitment in the education of the children 2) Implementation of parenting education through parenting seminars, parental consultation days, religious lectures, ‘madin mengaji’ activities using the ummi method, teacher visits to parents of students' homes 3) The results of the achievement of character building in Nurul Huda kindergarten include a) Students were accustomed to saying greetings, b) students were polite, c) students were highly integrated d) the students concerned for their environment.